Effects of oleic acid and/or exercise on diet-induced thermogenesis and obesity in rats: involvement of beige adipocyte differentiation and macrophage M1 inhibition - Abeer Salama; Mohamed M Amin; Azza Hassan (Research in Pharmaceutical Sciences, 2023)
Background and purpose: Obesity is a public health problem and the existence of beige adipocytes has got interested as a potential therapeutic involvement for obesity and obesity-associated diseases. Adipose tissue M1 macrophage inhibition, also, has a vital role in obesity via down-regulating adipose tissue inflammation and the use of natural compounds such as oleic acid with exercise has been proposed. The present study aimed to evaluate the possible effects of oleic acid and exercise on diet-induced thermogenesis and obesity in rats. Experimental approach: Wister albino rats were categorized into six groups. Group I: normal control, group II: oleic acid group (9.8 mg/kg; orally), group III: high-fat diet (HFD), group IV: HFD plus oleic acid, group V: HFD plus exercise training, group VI: HFD plus exercise training and oleic acid. Findings/Results: Oleic acid administration and/or exercise significantly decreased body weight, TG, and cholesterol, as well as elevated HDL levels. Furthermore, oleic acid administration and/or exercise reduced serum MDA, TNF-α, and IL-6 levels, elevated the levels of GSH and irisin, increased the expression of UCP1, CD137, and CD206, and reduced CD11c expression. Conclusion and implications: Oleic acid supplementation and/or exercise could be used as therapeutic agents for treating obesity via its antioxidant and anti-inflammatory activities, stimulation of beige adipocyte differentiation, and macrophage M1 inhibition.